Why Patient Centered Care Coordination Is Important in Developing Countries? - Otero, C.; Luna, D.; Marcelo, A.; Househ, M.; Mandirola, H.; Curioso, W.; Pazos, P.; Villalba, C. (Yearbook of Medical Informatics, 2015)
Patient Centered Care Coordination (PCCC) focuses on the patient health care needs. PCCC involves the organization, the patients and their families, that must coordinate resources in order to accomplish the goals of PCCC. In developing countries, where disparities are frequent, PCCC could improve clinical outcomes, costs and patients satisfaction.Objective: the IMIA working group Health Informatics for Development analyzes the benefits, identifies the barriers and proposes strategies to reach PCCC.Methods: Discussions about PCCC emerged from a brief guide that posed questions about what is PCCC, why consider PCCC important, barriers to grow in this direction and ask about resources considered relevant in the topic.Results: PCCC encompasses a broad definition, includes physical, mental, socio-environmental and self care. Even benefits are proved, in developing countries the lack of a comprehensive and integrated healthcare network is one of the main barriers to reach this objective. Working hard to reach strong health policies, focus on patients, and optimizing the use of resources could improve the performance in the devolvement of PCCC programs. International collaboration could bring benefits. We believe information IT, and education in this field will play an important role in PCCC.Conclusion: PCCC in developing countries has the potential to improve quality of care. Education, IT, policies and cultural issues must be addressed in an international collaborative context in order to reach this goal.
Keywords: Patient centered care coordination; health information system; information technology; developing countries